Cryosphere carbon dynamics control early Toarcian global warming and sea level evolution - Ruebsam, W.; Mayer, B.; Schwark, Lorenz (Elsevier Science BV, 2019)
© 2018 The Earth's cryosphere represents a huge climate-sensitive carbon reservoir capable of releasing carbon dioxide (CO2) and methane (CH4) from permafrost soils or gas reservoirs capped by permafrost and ice caps upon rising global temperatures. Carbon release from these reservoirs has the potential to further accelerate global warming. Present day cryosphere demise is a focus of scientific research. The potential role of cryosphere carbon reservoirs in Mesozoic climate perturbations is even lesser known and currently underinvestigated. In contrast to previous views of a constantly warm Early Jurassic period, virtually lacking a cryosphere, recent studies have identified icehouse conditions for this time interval. Following these icehouse conditions, global warming occurred during the early Toarcian (~183 Ma) and was accompanied by a major carbon cycle anomaly as manifested in recurring negative carbon isotope excursions (CIEs). We propose that an initially volcanic-driven gentle rise of atmospheric temperature in the Early Toarcian triggered a melt-down of Earth's cryosphere which during the preceding Pliensbachian had expanded to the mid-latitudes and thus was highly vulnerable to warming. The rapid release of greenhouse gases, mainly as 13C-depleted CH4, or its oxidation product CO2, is recorded in the carbon isotope ratios of sedimentary organic matter and carbonates. Toarcian sediments display a series of orbitally-forced negative CIEs characterized by a frequency shift from eccentricity to obliquity cycles comparable to Pleistocene climate rhythms. This pattern is explained by a self-sustaining destabilization of labile cryosphere carbon reservoirs which started at mid-latitudes where eccentricity is most effective and then rhythmically progressed poleward to latitudes where obliquity dominates. The hitherto underestimated presence of a temperature-sensitive Pliensbachian cryosphere constituted an essential precondition for the early Toarcian climate change and its associated sea-level rise. The Pliensbachian cooling had transferred water into the terrestrial cryosphere causing a severe sea-level fall. Transgressive pulses at the Pliensbachian-Toarcian boundary and in the early Toarcian occurred concomitant to rising global temperatures and resulted from the meltdown of continental ice caps. This ice-volume effect and the massive discharge of freshwater into the oceans is well preserved in the exceptionally low d18O values of carbonates formed during the cryosphere demise and sea-level increase. Carbon and oxygen isotope ratios, climate and sea-level shifts thus underpin the presence of an Early Jurassic cryosphere and thereby highlight the role of glacio-eustatic mechanisms as main drivers of late Pliensbachian to early Toarcian geodynamics.